Internal Tide Cycle and Topographic Scattering Over the North Mid‐Atlantic Ridge. Issue 12 (2nd December 2020) - Lahaye, Noé; Gula, Jonathan; Roullet, Guillaume
Abstract: Internal tides are a predominant source of high‐frequency variability and diapycnal mixing in the ocean. Understanding their dynamics and lifecycle is necessary to better understand their role in the ocean circulation. In this study, we describe and quantify internal tide generation, propagation, and dissipation in a sector of the North Mid‐Atlantic Ridge, using high‐resolution numerical simulations with realistic bathymetry and stratification. We show that the generation and dissipation of internal tides, as well as the distribution of internal tides among vertical modes, exhibit high spatial variability. We find that topographic scattering leads to a significant transfer of energy toward high vertical modes and thereby enhances internal tide dissipation. On average, and especially on the ridge, this mechanism is dominant over the conversion from the barotropic tide for transferring energy to high ( > 7) vertical modes. The magnitude of the scattering of the first baroclinic internal mode is found to be in good agreement with theoretical predictions. Plain Language Summary: Internal waves are dynamical perturbations propagating throughout the stratified ocean. The internal waves generated by the interaction of the astronomical tide with the seafloor, the so‐called "internal tides, " are ubiquitous in the ocean. They are a predominant source of high‐frequency variability and mixing. Understanding their dynamics and lifecycle is necessary to better understand their role in the ocean circulation. Here, we describe and quantify the internal tides generation, propagation and dissipation in a sector of the North Mid‐Atlantic Ridge, using high‐resolution numerical simulations with realistic bathymetry and stratification. We find that the interaction of the internal tide with the topography, leading to topographic scattering, is an important mechanism for dissipating internal tides energy. Key Points: The lifecycle of internal tides is described and quantified over a region of the North Mid‐Atlantic Ridge Topographic scattering significantly transfers energy to high vertical modes, thus enhancing dissipation Topographic scattering is a first order mechanism over the ridge, which acts as a net sink of energy for the internal tides